Optimization of dichloroacetic acid hydrogenation reactor - A. G. Loshchev; E. A. Glushachenkova; Yu. A. Pisarenko; A. Yu. Zakgeim (Тонкие химические технологии, 2008)
In this article the optimal operating modes of the dichloroacetic acid hydrogenation reactor by experimental design method have been defined, providing both the high purity of commercial monochloroacetic acid and rational, using of the expensive palladium activated charcoal-based catalyst. The optimal methods of sectioning and additional irrigation of the reactor have been proposed.